Non-Epithelial Stromal Cells in Thymus Development and Function - James, Kieran D.; Jenkinson, William E.; Anderson, Graham (Frontiers in Immunology, 2021)
The thymus supports T-cell development via specialised microenvironments that ensure a diverse, functional and self-tolerant T-cell population. These microenvironments are classically defined as distinct cortex and medulla regions that each contain specialised subsets of stromal cells. Extensive research on thymic epithelial cells (TEC) within the cortex and medulla has defined their essential roles during T-cell development. Significantly, there are additional non-epithelial stromal cells (NES) that exist alongside TEC within thymic microenvironments, including multiple subsets of mesenchymal and endothelial cells. In contrast to our current understanding of TEC biology, the developmental origins, lineage relationships, and functional properties, of NES remain poorly understood. However, experimental evidence suggests these cells are important for thymus function by either directly influencing T-cell development, or by indirectly regulating TEC development and/or function. Here, we focus attention on the contribution of NES to thymic microenvironments, including their phenotypic identification and functional classification, and explore their impact on thymus function.